Venetoclax durable response in adult relapsed/refractory Philadelphia-negative acute lymphoblastic leukemia with JAK/STAT pathway alterations - Ferrari, Anna; Cangini, Delia; Ghelli Luserna di Rorà, Andrea; Condorelli, Annalisa; Pugliese, Marta; Schininà, Giovanni; Cosentino, Sebastiano; Fonzi, Eugenio; Domizio, Chiara; Simonetti, Giorgia; Leotta, Salvatore; Milone, Giuseppe; et al. (Frontiers in Cell and Developmental Biology, 2023)
High-risk-relapsed/refractory adult Philadelphia-negative (Ph-) B-cell acute lymphoblastic leukemia (B-ALL) is a great challenge due to limited possibilities to achieve and maintain a complete response. This also applies to cases with extramedullary (EM) involvement that have poor outcome and no accepted standard therapeutic approaches. The incidence of EM localization in relapsed/refractory B-ALL is poorly investigated: data on patients treated with blinatunomab reported a 40% rate. Some responses were reported in EM relapsed/refractory B-ALL by inotuzumab ozogamicin or CAR-T treatments. However molecular mechanisms of response or refractoriness are usually investigated neither at medullary nor at EM sites. In the complex scenario of pluri-relapsed/refractory B-ALL patients, new target therapies are needed. Our analysis started from the case of an adult pluri-relapsed Ph- B-ALL patient, poorly sensitive to inotuzumab ozogamicin, DLI and blinatumomab in EM disease, who achieved a durable/complete response after treatment with the BCL2-inhibitor venetoclax. The molecular characterization of medullary and EM samples revealed a tyrosine kinase domain JAK1 mutation in bone marrow and EM samples at relapse. By comparing the expression level of BCL2- and JAK/STAT pathway-related genes between the patient samples, 136 adult JAK1wt B-ALL and 15 healthy controls, we identified differentially expressed genes, including LIFR, MTOR, SOCS1/2, BCL2/BCL2L1 that are variably modulated at the diverse time-points and might explain the prolonged response to venetoclax (particularly in the EM site, which was partially affected by previous therapies). Our results suggest that the deep molecular characterization of both medullary and EM samples is fundamental to identify effective and personalized targeted therapies.